Diagnóstico empresarial y plan de mejoramiento de la empresa COMERCIAL FÉNIX S.A.S (2024)
The document presents the business diagnosis of the company Comercial Fénix S.A.S, with the objective of identifying its current situation and proposing an improvement plan. An internal analysis is carried out that reveals strengths such as a committed team and weaknesses in process management and internal control. The external analysis highlights a competitive environment, where Comercial Fénix S.A.S faces opportunities for expansion and threats due to increasing competition and regulatory changes. Based on these findings, an improvement plan is proposed that includes the implementation of a quality management system, the adoption of technologies to optimize processes and staff training. The document concludes that, by executing this plan, Comercial Fénix S.A.S can overcome its weaknesses, take advantage of opportunities and strengthen its competitive position in the market. The importance of a strategic approach that integrates internal and external analysis to guide the development of the company and ensure its sustainable growth is emphasized.